ESTUDO DE DIRETRIZES PARA AVALIAÇÃO DE MATURIDADE DE PROCESSOS: O CASO DE UMA EMPRESA DE ENERGIA - Herkenhoff, Débora Athayde (2011)
The global dynamic requires business process management efficiently and seek to optimize processes and achieve more consistent results. The number of companies are adopting business process management has grown significantly in recent years. Despite difficulties such as inexperience and lack of reference to deal with the process management is essential that this be sustained by the use of best practices and compatible tools to improve management and achieve better performance. A maturity model provides information processes that guide the company in defining its improvement plan and the choice of practices compatible with your business and stage of maturity where it is. Thus, the search is performed for the evaluation of the maturity of management processes and contribute to the difficulty of the companies to identify strengths and weaknesses of models currently available, to use a model is appropriate and the reality of your business . The methodology used was based on a literature review on the business process maturity assessment, supported by a field research carried out by applying a questionnaire and interviews held in a energy company. It was observed the difference between the criteria used by each model in the evaluation and concluded the importance of the use of guidelines for application of a model for assessing the maturity and care in selecting the model according to business needs for the company to achieve better results in their projects. The research finally presents guidelines for application of a model of maturity assessment, using the information gathered from the survey